Paediatricians' attitudes toward pain in children with severe cognitive impairment. A regional survey - E. Barbi; L. Badina; M. Massaro; G. Pisciotta; A. Ventura (PAGEPress Publications, 2014)
Introduction: pain is a frequent and relevant problem in children with severe cognitive impairments. Assessing pain in these patients can be difficult. Specific observational tools such as the Collignon Giusiano Questionnaire or the Non-communicating Children's Pain Checklist ( NCCPC) are available, but their use is not widespread. Children with severe cognitive impairment are frequently in need of painful procedures but data about availability of procedural sedation in this setting are limited. Objective of the study: to evaluate paediatricians' attitudes toward pain in children with severe cognitive impairment by measuring the use of specific pain scales and the use of analgesia or procedural sedation in course of a frequent procedure such as botulinum toxin injection. Methods: phone interview with the doctor on duty of 56 paediatric wards in 3 regions of the North East of Italy, addressing the routine use of pain scales, and the use of specific observational tools for non communicating children. A phone interview was also conducted in 4 centers routinely practicing botulinum toxin injection about the use of analgesia or procedural sedation. Results: 1 centre out of 55 reported to use specific scales for children with cognitive impairment, specifically the Collignon Giusiano Questionnaire. No centre used procedural sedation for botulinum toxin injection. Conclusion: in the investigated area there is a lack of attention to pain in children with severe cognitive impairment. Specific educational efforts should be done to improve the quality of care in this setting.